Assessment of Patient Satisfaction in Relation to Postoperative Morbidity After Surgical Removal of Impacted Third Molars - Aylin Calis; Yıldız Ünüvar; Zelal Gündüz; Candan Efeoğlu; Banu Özveri Koyuncu (Selcuk Dental Journal, 2026)
Background: Impacted third molar extraction is a common oral surgical procedure, and beyond surgical outcomes, patient satisfaction is an important indicator of care quality. This study aimed to evaluate patient satisfaction, postoperative complications, and factors influencing these outcomes.Materials and Methods: A total of 369 patients who underwent impacted mandibular or maxillary third molar extraction between July 2022 and November 2023 at Ege University were included. Demographic characteristics, preoperative symptoms, surgical details, and complications were recorded. The Pell and Gregory classification was used for mandibular molars. Satisfaction was assessed using a Numeric Rating Scale (NRS) and a survey addressing patients’ experiences with the procedure. Statistical analyses examined associations between demographic and clinical factors with satisfaction scores.Results: Among the patients, 30.62% were male and 69.38% female, with a mean age of 24.6 years. Preoperative symptoms were reported by 59.89%, most commonly pain (58.54%). Postoperative complications occurred in 27.91% of cases, primarily pain lasting longer than 72 hours (24.66%), trismus (7.32%), paresthesia (1.90%), and alveolitis (1.63%). Despite these complaints, overall satisfaction levels were high: 49.32% rated their experience as 10/10, and 96.75% expressed willingness to return to the clinic for future care.Conclusion: Although postoperative discomfort was frequent, patient satisfaction remained high. Effective communication, adequate pain management, and accessible postoperative support appear to play key roles in enhancing the patient experience. Incorporating patient-centered approaches may help further improve outcomes and satisfaction.Key words: third molar surgery; patient satisfaction; postoperative complications; oral surgery; visual analog scale.